Implementation of forest extension methods in improving the knowledge and skills of forest farmers in Maros District: Case study on forestry extension methods in Tompobulu District, Maros Regency - Andi Nur Imran; Nirawati; Andi Khairil A. Samsu (Foresty Faculty of Hasanuddin University, 2022)
The forestry extension method is a service system that helps the community, especially farmers and communities around the forest, in education, knowledge, implementation of techniques, and methods of utilizing and preserving forest resources. The study aimed to determine the forms of forestry extension methods in Tompobulu District and analyze the effect of forestry extension learning methods in increasing the knowledge and skills of forest farmers in Maros District. Data analysis was carried out to analyze forestry extension methods using qualitative descriptive analysis with a Likert scale. While the analysis used to analyze the forestry extension method in improving the knowledge and skills of forest farmers in Tompubulu District is quantitative analysis with t-test. The results of the study stated that the forestry extension methods implemented were 1) direct communication method, 2) method through teaching aids messages, 3) method based on individual approach, 4) method based on group approach, 5) participatory method, and 6) technology-based method, information, and communication (ICT). The effect of forestry extension methods that have a significant effect in increasing the knowledge and skills of forest farmers are direct communication methods, methods based on individual approaches, and participatory methods. At the same time, the methods that do not significantly affect the increase in knowledge and skills of forest farmers are the method through the message of teaching aids, the method based on the group approach, and the method based on technology, information, and communication (ICT)